2015
DOI: 10.1088/0004-637x/812/1/41
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Inner Disk Gas in Transition Disks

Abstract: Investigating the molecular gas in the inner regions of protoplanetary disks provides insight into how the molecular disk environment changes during the transition from primordial to debris disk systems. We conduct a small survey of molecular hydrogen (H 2 ) fluorescent emission, using 14 well-studied Classical T Tauri stars at two distinct dust disk evolutionary stages, to explore how the structure of the inner molecular disk changes as the optically thick warm dust dissipates. We simulate the observed HI-Lym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(100 citation statements)
references
References 125 publications
17
81
2
Order By: Relevance
“…All of these observations have been described previously in studies of H 2 (e.g. France et al 2012b;Hoadley et al 2015), hot gas (e.g. Ardila et al 2013), and UV radiation (e.g.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…All of these observations have been described previously in studies of H 2 (e.g. France et al 2012b;Hoadley et al 2015), hot gas (e.g. Ardila et al 2013), and UV radiation (e.g.…”
supporting
confidence: 57%
“…To explore the behavior of H 2 populations simultaneously in all PPD sightlines, we normalize each H 2 rotation diagram to the column density in the [v = 2,J = 1] level. We include thermal models of warm/hot distributions of H 2 populations, drawn through the normalization rovibrational level [v = 2,J = 1], which range from the expected thermal populations of fluorescent H 2 in PPDs (Herczeg et al 2002(Herczeg et al , 2006France et al 2012b;Hoadley et al 2015) to the dissociation limit of the molecule (red dashed line for T diss ≈ 4500 K; Shull & Beckwith 1982;Williams & Murdin 2000).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The thermal models at 1500 and 2500 K are unable to reproduce the flux in the (1 -4) R(12) line. It appears that the 3000 K spectrum can approximately describe the line complex near 1186Å, however this spectrum significantly overpredicts the observed data at other wavelengths, which is reflected in the results of previous fits to the H 2 spectrum, T (H 2 ) ≤ 2000K for V4046 Sgr (Hoadley et al 2015;McJunkin et al 2016). Emission from non-thermal H 2 is able to augment the dominant thermal population and present a better overall fit to the observed spectrum.…”
Section: Comparison Of the Synthetic H2o Dissociation Spectra With Thmentioning
confidence: 70%
“…found evidence for an insideout depletion sequence where CO gas is progressively removed from ∼0.1 out to ∼20 au, providing a new probe of gaps over a radial disk region that extends the region probed by millimeter interferometers (typically limited to 5 10 au -, depending on the distance from Earth). By tracing H 2 emission at ultraviolet wavelengths, Hoadley et al (2015) found similar evidence for a removal of molecular gas at small radii in transitional disks. The combination of dust and gas studies of small to large gaps bears the potential for a comprehensive understanding of the physical and chemical evolution of inner disks during planet formation.…”
Section: Introductionmentioning
confidence: 71%